(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: It is important for pediatric ophthalmologists to explore the keratometry parameters used in selection of contact lenses (and thus to improve visual function, quality of life, and treatment of complications of refractive errors) in premature children who received laser photocoagulation (LPC) to the avascular retina for threshold retinopathy of prematurity (ROP). Purpose: To assess the keratometry parameters in premature children who received LPC to the avascular retina for threshold ROP for the advanced improvement of visual functions and advanced treatment of complications of refractive errors in this category of patients. Material: We retrospectively examined the medical records (including automatic keratometry results) of 282 children (564 eyes). Results: There was a significant difference in corneal refractive power (CRP) in the steepest principal meridian and the flattest principal meridian between children of group 1 (i.e., premature children who received bilateral LPC) and group 2 (i.e., premature children who did not develop threshold ROP by the time retinal vascularization was complete) (р=0.00007 and р=0.0001, respectively) and between children of group 1 and group 3 (randomly selected full-term children) (р=0.000002 and р=0.000001, respectively), and mean CRP was higher in children who received LPC than in those who received no LPC. A significant difference in CRP between the steepest principal meridian and the flattest principal meridian (р=0.015) was found only for the comparison between the children who received LPC and controls. The value of this parameter was larger in children who received LPC than in full-term children. Conclusion: These findings may be helpful when selecting optical correction (e.g., orthokeratology correction) for refractive errors in the premature children who received LPC.